Current distributional status of the critically endangered valcheta frog: implications for conservation - Velasco, Melina Alicia (2016)
The Valcheta Frog, Pleurodema somuncurense (Cei, 1969), is a critically endangered species endemic from Somuncura plateau, Patagonia, Argentina. Although this frog is facing several human-related threats, the available information about its population status and trends is scarce. In order to update the range of the species, from 2013 to 2015, we conducted exhaustive surveys in all its geographical distribution, including sites never explored in the past. In 2014, we estimated occupancy and probability of detection with a three-visit survey in 40 sites of headwaters of Valcheta stream. Frogs were present in 58% of sites, and the probability of detection was high. We increased the known range of Valcheta Frog in 160%, by adding new sites occupied by the species. However, the status of the species remains of great concern, since its total range barely reaches 4 square kilometres. © 2016, Universidade do Vale do Rio dos Sinos. All rights reserved.